Simulation investigation of dent behavior of steel pipe under external load. (August 2018) - Han, Chuanjun; Tan, Sisi; Zhang, Jie; Zhang, Chuan
Abstract: Denting, caused by working condition and by rocks or external objects during the laying process, is an important failure mode of steel pipes. To study the failure mechanism of a steel pipe, steel pipe behavior with longitudinal, transverse, and tilted dents were investigated. Effects of the diameter-thickness ratio and indenter displacement on the pipe mechanical behavior were studied. The results showed that plastic deformation occurred mainly at the dent, where there was an obvious stress concentration. The plastic deformation of the pipe continued to increase during the unloading process. The axial strain at the dent location was compressive strain. Dent's rebound rate (depth ratio of the dent after loading and unloading) of the pipe increased with increasing the diameter-thickness ratio and decreased with increasing the indenter displacement. With transverse denting, both sides of the dent were more dangerous than the dent location. The force-displacement curve for the pipe subjected to a tilted dent was different than those for longitudinal and transverse denting. There is no raised effect for the tilted dent. Highlights: Behaviors of dented pipe subjected to different indenters were investigated. There is an obvious stress and strain concentration on the pipe's dent. Equivalent plastic strain of the pipe increases during the unloading process. There is no plateau stage in force-dent depth curve undergoing tilted indenting. Rebound rate increases with increasing the diameter-thickness ratio.